Disconnection or Unawareness: Professionals in Preschool Education and the Didactic of a Foreign Language - Jaramillo-Valencia, Bairon; Quintero-Arrubla, Sonia Ruth (Revista Electrónica Educare, 2022)
Objective. This paper aims to show how important theoretical knowledge is for the theory and practice of teaching English –as a foreign language– for early childhood teachers. Method. The respective research was named Pedagogical training of professionals in early childhood education and how it is related to didactics in an international context. Likewise, a qualitative paradigm was used to present the effects and data collected from the surveys and the statements from the units of analysis that took part in the semi-structured interviews and focus groups. The participants were 200 professionals in early childhood education (100 from Colombia and 100 from Mexico). Results. Among the most meaningful results, it was found that it is necessary to implement didactic courses about teaching English to children in undergraduate degrees related to training professionals for early childhood education. Moreover, it was visible the phenomenon of giving priority to hiring English teachers –to teach in preschool– compared to employing early childhood teachers. Conclusions. The English levels certificates that the early childhood teachers obtained, apart from their studies in the university, did not guarantee any didactic knowledge to teach this language to children. Similarly, all kinds of knowledge about theory and pedagogical approaches, in general, are tools considered not sufficient to supply the gaps in the teaching practice in this language.